Laparoscopic Testicular Preservation in Adults with Intra-Abdominal Cryptorchidism: Is It Beneficial? - Fábio César Miranda Torricelli; Marco Antonio Arap; Ricardo Jordão Duarte; Anuar Ibrahim Mitre; Miguel Srougi (Advances in Urology)
Purpose. To present the results in a midterm followup of laparoscopic testicular preservation in adults with intra-abdominal cryptorchidism. Methods. We analyzed 14 adult patients with cryptorchidism (19 testes) submitted to transabdominal laparoscopic evaluation and treatment of the condition. Data was collected retrospectively from a prospective database from August 2005 to May 2010. It analyzed patient age, affected side, procedure, mean operative time, mean hospital stay, postoperative testis position, intra- and postoperative complications, presence of malignancy in the removed testis, and midterm outcomes: size of the testis, development of tumors, and fertility. Results. Mean patient age was 29 (18–54) years. Thirteen (68.4%) testes were preserved. There were no intra- or postoperative complications. After a mean followup of 48.7 (20–64) months, all patients submitted to orchiopexy had the organs correctly positioned, although 2 testes were significantly smaller than before the procedure. No patient presented any signs of malignancy during the followup. Fertility was not preserved in bilateral cases. Conclusion. Laparoscopic testicular evaluation and eventual preservation are feasible and safe. In a midterm followup, testicular tumor is not a concern, and unfortunately, fertility may not be preserved in bilateral cases.